Changes in inflammatory gene expression in brain tissue adjacent and distant to a viable cyst in a rat model for neurocysticercosis. - Rogger P Carmen-Orozco; Danitza G Dávila-Villacorta; Ana D Delgado-Kamiche; Rensson H Celiz; Grace Trompeter; Graham Sutherland; Cesar Gavídia; Hector H Garcia; Robert H Gilman; Manuela R Verástegui; Cysticercosis Working Group in Peru (Public Library of Science (PLoS), 2021)
Background The parasite Taenia solium causes neurocysticercosis (NCC) in humans and is a common cause of adult-onset epilepsy in the developing world. Hippocampal atrophy, which occurs far from the cyst, is an emerging new complication of NCC. Evaluation of molecular pathways in brain regions close to and distant from the cyst could offer insight into this pathology. Methods Rats were inoculated intracranially with T. solium oncospheres. After 4 months, RNA was extracted from brain tissue samples in rats with NCC and uninfected controls, and cDNA was generated. Expression of 38 genes related to different molecular pathways involved in the inflammatory response and healing was assessed by RT-PCR array. Results Inflammatory cytokines IFN-γ, TNF-α, and IL-1, together with TGF-β and ARG-1, were overexpressed in tissue close to the parasite compared to non-infected tissue. Genes for IL-1A, CSF-1, FN-1, COL-3A1, and MMP-2 were overexpressed in contralateral tissue compared to non-infected tissue. Conclusions The viable cysticerci in the rat model for NCC is characterized by increased expression of genes associated with a proinflammatory response and fibrosis-related proteins, which may mediate the chronic state of infection. These pathways appear to influence regions far from the cyst, which may explain the emerging association between NCC and hippocampal atrophy.